2002
DOI: 10.1254/jjp.88.133
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nicotinic Receptor and Psychiatric Disorders: Functional and Behavioral Effects of Nicotine

Abstract: ABSTRACT-Both retrospective and prospective clinical studies have demonstrated positive associations of smoking with psychiatric disorders such as schizophrenia, depression and anxiety. Neuronal nicotinic acetylcholine receptors (nAChR) belong to a family of ligand-gated ion channels that are widely distributed in the brain. The pre-synaptically located nAChR, which are composed of =3 or =4 subunits in combination with >2 subunit on axon terminals, modulate the multiple transmission release. Several studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…6, bottom). Jonnala and Buccafusco, 2001;Shimohama and Kihara, 2001), and to serve as a potential drug target in disease states such as schizophrenia (Marutle et al, 2001;Araki et al, 2002), epilepsy (Gil et al, 2002), Alzheimer's disease (Briggs et al, 1997;Meyer et al, 1997;Kem, 2000), and Parkinson's disease (Burghaus et al, 2003). As new ␣7nAChR compounds become available it would be advantageous to have an efficient, objective, and experimentally simple model for drug efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…6, bottom). Jonnala and Buccafusco, 2001;Shimohama and Kihara, 2001), and to serve as a potential drug target in disease states such as schizophrenia (Marutle et al, 2001;Araki et al, 2002), epilepsy (Gil et al, 2002), Alzheimer's disease (Briggs et al, 1997;Meyer et al, 1997;Kem, 2000), and Parkinson's disease (Burghaus et al, 2003). As new ␣7nAChR compounds become available it would be advantageous to have an efficient, objective, and experimentally simple model for drug efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the concentration and task, an increase in cholinergic transmission, for example via smoking, produces improvements of cognitive functions like memory and attention [2,7,14,37,58,67], whereas blocking cholinergic transmission impairs cognition [15,32,35,43,51,65,73].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies indicated that tobacco smoking may represent a form of self-medication in some psychiatric diseases [5][6][7][8]. However, the use of nicotine in therapy is severely limited by its carcinogenic and cardiovascular side effects.…”
Section: Introductionmentioning
confidence: 99%